Kontribusi Pesantren Wilayah Perbatasan Dalam Pendidikan dan Relasi Antar Umat Beragama di Kabupaten Aceh Tamiang - siti nur zalikha (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine the contribution of border region Islamic boarding schools in education and relations between religious communities in Aceh Tamiang district. This research used descriptive qualitative methods and was conducted to see whether Dayah Border Manarul Islam is an institution that can prevent conflicts between religious communities. Based on the research that has been carried out, it was found that the relationship between Dayah Manarul Islam and the surrounding community is good, marked by a relationship of mutual trust and social cooperation between the two. Relations between religious communities are also going well, characterized by minimal conflict between religious gatherings on the borders of Aceh Tamiang Regency. Educational institutions such as Dayah Border Manarul Islam can be a means of minimizing the potential for friction between religious communities in border areas. In conclusion, the contribution of Islamic boarding schools in border areas to education and relations between religious communities. Keywords: border empowerment, education, relations between religious communities